Assessing the effects of seasonal grazing on holm oak regeneration: Implications for the conservation of Mediterranean dehesas - Carmona, Carlos P.; Azcárate, Francisco M.; Oteros-Rozas, Elisa; González, José A.; Peco, Begoña (Biological Conservation, 2013)
Scattered trees in agricultural landscapes are globally declining due to the intensification of agricultural practices. Dehesas, highly species-diverse Mediterranean open woodlands, are seriously affected by this decline, because of a generalized regeneration failure of oak, which compromise their long-term stability. Traditionally, dehesas were the wintering areas for transhumant herds, but transhumance is disappearing in the Mediterranean, due to multiple causes. Reductions in grazing intensity or grazing abandonment have been proposed to improve oak regeneration in dehesas, but the effect of the recovery of non-continuous grazing practices such as transhumance has not been tested to date. We measured different indicators of holm oak regeneration and condition in dehesas under transhumant grazing and in dehesas under permanent grazing in southern Spain. Oak juveniles were remarkably less browsed and their canopies covered a much higher area in transhumant estates. As a consequence, the median density of saplings was more than four times higher in transhumant than in permanently-grazed estates. Although transhumant grazing is necessarily associated with a reduction in the stocking rate across the year, the timing of grazing was always included as a predictor in the best models to explain the condition and density of holm oak. Our results suggest that the lack of oak regeneration in dehesas can be caused not only by the increases in stocking rates, but also by the recent abandonment of traditional grazing practices like transhumance. We propose the recovery of seasonal grazing regimes based on transhumant pastoralism as a measure to improve the conservation status of dehesas.
Keywords: Agricultural intensification; Agroforestry; Browsing; Quercus ilex; Transhumance

Drove roads: Keystone structures that promote ant diversity in Mediterranean forest landscapes - Azcárate, Francisco M.; Seoane, Javier; Castro, Sara; Peco, Begoña (Acta Oecologica, 2013)
Abstract Drove roads are the traditional corridors used by pastoralists for seasonal movements of livestock (transhumance). They cover a considerable land area in Mediterranean countries and, although they are an obvious source of landscape diversity, their influence on the diversity and composition of animal assemblages has not been documented. Ant communities were studied on four active drove roads, two in forests (submediterranean and conifer) and two in open environments (croplands and rangelands). They were compared with the respective matrix communities and their contribution to local species richness was evaluated. The effects were heavily dependent on the open or closed nature of the matrix. In forest environments, drove roads increased ant species richness at the local scale, acting as clear keystone structures. Their species richness and functional diversity were highest on the fine scale, species composition was different, and a slight edge effect in the matrix was detected. In contrast, drove roads had little or even a negative effect in open environment locations. We conclude that drove roads have a high conservation value for ants in Mediterranean forest environments, in addition to their importance as reservoirs of plant biodiversity and generators of ecological goods and services.
Keywords: Ant assemblages; functional diversity; Grasslands; spatial heterogeneity; Transhumance

Grazing management or physiography? Factors controlling vegetation recovery in Mediterranean grasslands - Carmona, Carlos P.; Röder, Achim; Azcárate, Francisco M.; Peco, Begoña (Ecological Modelling, 2013)
Grazing intensification and abandonment are increasing the risk of degradation of Mediterranean grasslands. The development of techniques for monitoring grazing effects on herbaceous vegetation is an essential need for the management of these rangelands. However, the high variability of these systems make physiographical and management effects hard to disentangle and quantify. We present a methodology to support rangeland management and assess grazing effects on environmentally heterogeneous areas, and provide an example of its application in a Mediterranean rangeland in central Spain. We evaluated the difference in photosynthetically active vegetation cover between spring and summer using Spectral Mixture Analysis of very high spatial resolution (2.4 m) Quickbird images. To analyze this difference, we developed Boosted Regression Trees models using grazing management (accumulated cost distance to points of livestock concentration and water points) and physiographical variables (slope, wetness, proximity to the closest tree and orientation). Results show that the main factor determining changes in vegetation cover is habitat type. The magnitude of this change was maximized at intermediate grazing pressures for humid habitats, suggesting the existence of an optimal level of grazing in this zones, while in dry habitats differences in vegetation cover increased consistently along with grazing pressure. Our models provided a valuable insight into how different variables and its interactions affect the observed recovery capacity of vegetation. Moreover, by identifying areas in which grazing-induced land degradation could be taken place, our methodology can be used as a powerful tool in the management of highly heterogeneous rangelands.
Keywords: Boosted Regression Trees; Cost surfaces; Grazing gradients; Mediterranean; Rangeland management; Spectral Mixture Analysis

Abandonment of grazing in a mediterranean grassland area: consequences for ant assemblages - Azcárate, Francisco M.; Peco, Begoña (Insect Conservation and Diversity, 2012)
1. Abandonment of traditional activities in the rural areas is widespread in the developed world, and in the case of grazing, it is known to have negative consequences on the diversity of plant communities. Few studies have examined the impact of grazing abandonment on fauna, which in the case of ants is of considerable interest, given their usefulness as an indicator for monitoring environmental change. 2. Here, we present the results of a study conducted in Mediterranean grasslands of central Spain. Using pitfall traps, ants were sampled from 10 40 m· 20 m plots; ﬁve of them located in grazed systems and ﬁve in abandoned grazing systems. Descriptors used for the ant assemblage were ant species composition, ant species richness, ant functional groups, and subguilds of granivores. We used a seed bait test to discriminate between granivorous and non-granivorous ant species. 3. Our results show that abandoned grazing systems have more ant species and more heterogeneous ant assemblages. Changes in ant species composition and ant functional groups are more pronounced in habitats where woody encroachment progresses more rapidly (i.e. dry sectors and tree islands). Specialised granivores have reduced importance in the same habitat types. Conversely, facultative granivores increase their presence in abandoned grazing systems. 4. The increased functional and species ant diversity observed with grazing abandonment can be explained by the generation of a more heterogeneous environment at the smaller scales, in spite of being more homogenous at the larger scales, because the latter are less signiﬁcant for the organisms studied
Keywords: ant functional groups; Ants; Granivory; grazing abandonment; mediterranean grasslands

Drove roads as local biodiversity reservoirs: effects on landscape pattern and plant communities in a Mediterranean region - Azcárate, Francisco M.; Robleño, Irene; Seoane, Javier; Manzano, Pablo; Peco, Begoña (Applied Vegetation Science, 2012)
Question: What are the effects of traditional drove roads on landscape pattern and plant communities? Location: Madrid Autonomous Region, Central Spain. Methods: We selected four study localities in different landscape units. Within each locality, we selected eight sites and within each site, we established three 1-ha plots, each corresponding to one of three situations: drove road, adjacent matrix or distant matrix. The landscape pattern of each plot was characterized by the cover of the different patch types, the patch type richness ha 1 and the patch type evenness ha 1 . At one site per locality, we also recorded vegetation by randomly distributing twenty 20 cm 9 20 cm quadrats per plot. We characterized each quadrat by its species richness, plant species composition and plant functional composition. We also analysed species richness by constructing rarefaction curves for each plot. Results: In the localities situated in croplands, sub-mediterranean forests and coniferous forests, drove roads were found to be an important source of spatial heterogeneity and a reservoir for a large number of plant species. In contrast, drove roads did not differ from the matrix habitats in rangelands, suggesting that the processes shaping drove road vegetation are similar to the general processes that shape grazed systems. Drove roads did not imply a signiﬁcant increase in functional diversity. Our results were heavily scale-dependent: while drove roads provided heterogeneity at the local scale, they showed a remarkable similarity at the large scale. Conclusions: Drove roads act as authentic local biodiversity reservoirs, especially in environments with low grazing levels. At the same time, drove roads imply structural and functional continuity on a large scale, increasing potential connectivity at the regional level. We recommend the preservation of drove roads in a functional state, because of their beneﬁts to plant biodiversity conservation, and claim that these beneﬁts should be considered when designing livestock policies with different intensiﬁcation scenarios.
Keywords: extensive grazing; functional diversity; functional traits; landscape heterogeneity; Transhumance

Testing the role of seed size in annual legume seedling performance under experimental autumn moisture conditions - Arellano, Gabriel; Peco, Begoña (Journal of Vegetation Science, 2012)
Question: Previous studies show that large-seeded species increase their abundance in Mediterranean annual grasslands in growing seasons with dry autumns. One possible explanation is that large-seeded species have larger seedlings, which provide an advantage under drier conditions. We address the following questions: is seed mass correlated with seedling survival in annual legumes? Is this correlation inﬂuenced by the watering regime? Can seedling growth characteristics explain the differential survival of small- and large-seeded species? Location: Annual Mediterranean grassland, Central Spain. Methods: An experiment was conducted with six grassland legume species of different seed sizes, subjected to six different watering regimes, monitoring survival and morphological variables (shoot and root growth) for 40 d. Results: Large seeds provide an advantage for seedling survival, but in extreme drought conditions, seedling survival in small-seeded species equals that of seedlings from large-seeded species. Seedlings from larger seeds are larger than those of small-seeded species, but have a lower root/shoot biomass ratio, leading to greater potential evapotranspiration, which could explain their loss of relative advantage under extreme droughts. Conclusion: The hypothesis that seedlings from large-seeded species survive better than small-seeded species under drought conditions was not supported. Germination behaviour seems to be a more plausible explanation for the increased abundance in the ﬁeld of large-seeded species in growing seasons with dry autumns.
Keywords: autumn drought; mediterranean therophytes; Pasture legumes; seed mass; seedling survival